Mutations of fake weighted projective spaces - Coates, Tom; Gonshaw, Samuel; Kasprzyk, Alexander M.; Nabijou, Navid (Electronic Journal of Combinatorics, 2014)
We characterise mutations between fake weighted projective spaces, and give explicit formulas for how the weights and multiplicity change under mutation. In particular, we prove that multiplicity-preserving mutations between fake weighted projective spaces are mutations over edges of the corresponding simplices. As an application, we analyse the canonical and terminal fake weighted projective spaces of maximal degree.